Причины многозначности абстрактных отглагольных имен действия английского языка - Янулявичене, Виолета (Kalbotyra, 1988)
The aim of the present article is to investigate different meanings of English abstract verbal nouns. The author deals with the problem or their origin, whether they are the result of word-formation process or instances of regular polysemy. Contrary to the assumption of several investigators who consider abstract and concrete meanings of verbal nouns to be separate homonymous words, the author regards those different meanings as constituents of the semantic structure of a polysemantic word. Polysemy may have lexical, derivational or mixed character.